The generation of a swimming pool cadastre for Graz (1945–2015) - Droin, Ariane; Sulzer, Wolfgang; Wecht, Matthias (Journal for Geography, 2016)
This paper deals with the generation of a swimming pool cadastre for Graz by means of multitemporal analyses of aerial photographs. Twelve temporal steps between 1944/45 and 2015 are analysed partly by digital image processing and visual mapping. The result shows an enormous increase of private swimming pool between the 1990 (600) and 2015 (5600). The distribution of swimming pools and their different types shows specific patterns, which can be geographically interpreted by social settlement structures.
Keywords: aerial photography; cadastre; social structure; Graz